دور الاسرة في عملية التنشئة السياسية - غربي, خالد; براك, خضرة (جامعة الوادي - University of Eloued, 2018)
التربية السياسية جزء أساس من التربية الشاملة للفرد والمجتمع ، وهذه التربية السياسية واجب اليوم ؛ من أجل إعداد فرد مواطن صالح ، فالتربية السياسية تعد المواطنين لممارسة الشئون العامة في ميدان الحياة ، عن طريق الوعي والمشاركة ، وعن طريق إعدادهم لتحمل المسؤولية ، وتمكينهم من القيام بواجباتهم، والتمسك بحقوقهم ، وتبدأ التربية السياسـية في مرحلة مبكرة من العمر ، وتستمر خلال سـنوات العمر كله, ولا بد أن تسهم جميع المؤسسات التربوية في المجتمع كالأسرة والمدرسة والأندية ووسائل الإعلام من صحافة وإذاعة وتلفزة ، والجامعات والمكتبات العامة , في إعداد المواطن إعداداً سياسياً, وتعد الاسرة هي المؤسسة التربوية الاولى فالفرد يكتسب من اسرته لغة المجتمع وعاداته وتقاليده واعرافه وقيمه فهي مؤسسة اجتماعية تمثل الجماعة الاولى للفرد ومنها يكتسب اول عضوية له في جماعة وتساهم في رعاية الفرد وتهذيبه وتؤثر في تكوين شخصيته وتموين اتجاهاته وقيمه وافكاره, وهي من اهم عوامل التربية السياسية وادواتها, وهي الممثل الاول للثقافة وتقدم للفرد تطبيعا اجتماعيا, وهي الوحدة المرجعية للفرد فهي التي يستمد منها هويته وكيانه ومكانته الاجتماعية واحيانا كثيرة مركزه السياسي وتؤدي دورا رئيسيا في عملية التربية السياسية, حيث تغرس في اطفالها منذ نعومة اظافرهم معاني الوطنية والولاء واحت ا رم السلطة وتحدد لهم الهوية التي يؤمنون بها . وقد جاءت هذه المقالة لتبين الدور الذي تلعبه الأسرة الجزائرية في تشكيل الاتجاهات والآراء السياسية للفرد وكيف يكسب الفرد صفة المواطنة؟ Political education based on comprehensive education of the individual and society part, these political education is the duty of the day; in order to prepare an individual good citizen, political education is a longer citizens to the exercise of public affairs in the life field, through awareness and participation, and by preparing them to take responsibility, enabling them to carry out their duties, and uphold their rights, and the start of political education at an early stage of life, and continue during the years the whole life, and must contribute to all educational institutions in the community, such as family, school, clubs and the media of the press, radio and television, universities and public libraries; the preparation elmo Tons politically prepared, the family is the first educational institution the individual acquires from his family, the language of society and its customs, traditions and customs, and values, it is a social institution that represents the first group of the individual, which is gaining its first membership of his group and contribute to the care of the individual and refine and affect the composition of his character and Supply trends, values and ideas, a The most important factors of political education and its tools, the first representative of culture and provides the individual social normalization, which is the reference unit of the individual is derived from the identity and entity and social status and often have a political center and play a key role in the process of political education, Their children from the very beginning of their nails have the meanings of patriotism, loyalty, respect for authority, and identification of the identity they believe in. This article came to show the role played by the Algerian family in shaping the political attitudes and views of the individual and how does the individual gain the status of citizenship?
The role of the family in the process of political upbringing
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: التنشئة السياسية, الاسرة; Political upbringing, family